Endosaccular Flow Disruption: A New Frontier in Endovascular Aneurysm Management - Dmytriw, Adam A (Neurosurgery, 2020)
Flow modification has caused a paradigm shift in the management of intracranial aneurysms. Since the FDA approval of the Pipeline Embolization Device (Medtronic, Dublin, Ireland) in 2011, it has grown to become the modality of choice for a range of carefully selected lesions, previously not amenable to conventional endovascular techniques. While the vast majority of flow-diverting stents operate from within the parent artery (ie, endoluminal stents), providing a scaffold for endothelial cells growth at the aneurysmal neck while inducing intra-aneurysmal thrombosis, a smaller subset of endosaccular flow disruptors act from within the lesions themselves. To date, these devices have been used mostly in Europe, while only utilized on a trial basis in North America. To the best of our knowledge, there has been no dedicated review of these devices. We therefore sought to present a comprehensive review of currently available endosaccular flow disruptors along with high-resolution schematics, presented with up-to-date available literature discussing their technical indications, procedural safety, and reported outcomes.